Les réseaux de femmes entrepreneures : des ressources face à la vulnérabilité et des espaces d’empowerment ? - Delphine Dupré; Claire d’Hennezel (Communication)
The literature on gender at work shows that male/female inequalities are shaped by symbolic, relational, communicational, and organizational mechanisms. Access to network resources is a key factor. In France, as of the 2000s, mechanisms of informal women’s networks were created as the “female counterpart” to male networks. We examine the mechanisms targeting women entrepreneur networks and, from a communications perspective, seek to determine if the exchanges within them can help remedy a certain “relational vulnerability” due to solitude, a lack of understanding by peers, and the specific professional problems women entrepreneurs face. We also question whether this female “enclaving” can be a factor of empowerment, or a “dynamic process fostering an awareness gained through an enlightened reading of the mechanisms of ordinary and organizational sexism.” Our analysis of 25 semi-structured interviews shows that networks foster the emergence of a supportive, caring female “enclave” conducive to moral support and work discussion spaces. Such networks also raise awareness of the roots of gender inequality, which sparks awareness initiatives in the entrepreneurial ecosystem. Lastly, we discuss the limitations that sap the emancipatory potential of these mutual support mechanisms.